The effect of the ProBalance Programme on health-related quality of life of community-dwelling older adults: A randomised controlled trial. (January 2018) - Gouveia, Bruna R.; Gouveia, Élvio R.; Ihle, Andreas; Jardim, Helena G.; Martins, Maria M.; Freitas, Duarte L.; Kliegel, Matthias
Highlights: The ProBalance RCT addressed HRQoL of community-dwelling older adults as outcome. The ProBalance intervention was effective in inducing robust effects on HRQoL. Effects of the 12-week training were independent of age and HRQoL component. The effect on HRQoL persisted after the 12-week no-intervention follow-up. Abstract: Background: Health-related quality of life (HRQoL) is an important health outcome in older adults. This study aimed to assess the efficacy of the ProBalance rehabilitation programme on HRQoL of community-dwelling older adults with balance impairments and to investigate whether effects differ between age groups and/or HRQoL components. Methods: A s ingle-blind, randomised controlled trial included community-dwelling older adults, aged 65–85, with balance impairments. Participants (n = 52) were randomly allocated to an intervention group (IG) or a control group (CG). A rehabilitation programme included gait, balance, functional training, strengthening, flexibility, and 3D training. A group-based intervention was administered over a period of 12 weeks (90-min sessions, 2 days per week). A wait-list control group was instructed to maintain their usual activities during the same period. Participants' HRQoL was assessed using the SF-36 questionnaire. The time points for assessment were at zero (pre-test), 12 (post-test), and 24 weeks (follow up). Results: A trend for higher HRQoL in the IG compared to the CG and a significant interaction of group with time were found, with significantly higher increases in HRQoL from the pre-test to the post-test (and to follow-up) in the IG, compared to the CG. Results: were independent of age group (young-old vs. old-old) and HRQoL component (physical vs. mental). Conclusions: Present results suggest that the ProBalance programme had a beneficial effect on HRQoL of community-dwelling older adults, which held across young and old adults and not only comprised physical but also mental HRQoL. Clinical Trial Registration Number: ACTRN12612000301864.